2010
DOI: 10.1111/j.1468-1331.2009.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of clock genes Per1 and Bmal1 in total leukocytes in health and Parkinson’s disease

Abstract: These results suggest that a peripheral molecular clock, as reflected in the dampened expression of the clock genes BMAL1 in total leukocytes, is altered in PD patients. In addition, the relative BMAL1 levels correlate positively with PD severity, which could provide a molecular basis to help monitor disease progression and response to investigational drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 30 publications
4
106
0
1
Order By: Relevance
“…This is supported by the evidence that Per2 mutant mice exhibit greater responsivity to cocaine (Abarca et al, 2002), drink more alcohol, and have higher levels of extracellular glutamate in the brain secondary to reduced glutamate uptake (Spanagel et al, 2005). Another idea, directly related to the present findings, is that the loss of circadian rhythms in clock gene expression in the striatum after DA depletion is linked to disruptions of daily behavioral and physiological rhythms frequently reported in Parkinson's disease (Bruguerolle and Simon, 2002;Cai et al, 2010). Current models posit that the symptoms of Parkinson's disease result from changes in excitability of striatopallidal neurons secondary to depletion of striatal DA (Day et al, 2006).…”
Section: Da Does Not Regulate Per2 In the Scnsupporting
confidence: 72%
“…This is supported by the evidence that Per2 mutant mice exhibit greater responsivity to cocaine (Abarca et al, 2002), drink more alcohol, and have higher levels of extracellular glutamate in the brain secondary to reduced glutamate uptake (Spanagel et al, 2005). Another idea, directly related to the present findings, is that the loss of circadian rhythms in clock gene expression in the striatum after DA depletion is linked to disruptions of daily behavioral and physiological rhythms frequently reported in Parkinson's disease (Bruguerolle and Simon, 2002;Cai et al, 2010). Current models posit that the symptoms of Parkinson's disease result from changes in excitability of striatopallidal neurons secondary to depletion of striatal DA (Day et al, 2006).…”
Section: Da Does Not Regulate Per2 In the Scnsupporting
confidence: 72%
“…To illustrate the importance of circadian regulation in PD, several studies have looked at central circadian pathway members. For example, a study done by Cai et al looked at expression levels of key components of the circadian rhythm machinery in leukocytes over a 12-h period in patients with and without PD (24). They found decreased levels of BMAL1, but not PER1, and further described a correlation between PD severity and BMAL1 expression levels (24).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…For example, a study done by Cai et al looked at expression levels of key components of the circadian rhythm machinery in leukocytes over a 12-h period in patients with and without PD (24). They found decreased levels of BMAL1, but not PER1, and further described a correlation between PD severity and BMAL1 expression levels (24). Another study found that BMAL2 also had significantly lower levels of expression in patients with PD than controls, suggesting a dysregulation of molecular clock components in patients with PD (44).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…And the relative Bmal1 level had a correlation with motor severity and sleep quality [89]. In addition, this group continued to check other key circadian genes in PD, and the results showed that the expression pattern of Bmal2, but not Clock or Dec1, was altered compared to controls [90].…”
Section: Clock Gene Differencementioning
confidence: 90%